Comparative analysis of PD-L1 expression between primary and metastatic pulmonary adenocarcinomas. (April 2017) - Kim, Sehui; Koh, Jaemoon; Kwon, Dohee; Keam, Bhumsuk; Go, Heounjeong; Kim, Young A; Jeon, Yoon Kyung; Chung, Doo Hyun
Abstract: Programmed death-ligand 1 (PD-L1) expression in pulmonary adenocarcinomas (pADCs) was implicated in predicting anti-PD-1/PD-L1 therapy efficacy. However, the differential expression of PD-L1 between primary and metastatic pADC remains unclear. Thus, we addressed this issue. In total, 161 paired primary and metastatic tumour tissues from 146 patients with pADC were collected. Most of the cases had regional nodal metastasis (134/161, 83.2%). PD-L1 expression was categorised based on the proportion of immunostained tumour cells using cutoff values of 1%, 5%, 10% and 50%. In primary tumours, PD-L1 positivity was observed in 28.1% (41/146), 27.4% (40/146), 22.6% (33/146) and 13.0% (19/146) of cases using cutoff values of 1%, 5%, 10% and 50%, respectively. The overall concordance rate for PD-L1 expression between primary and metastatic tumours was 75.2% (121/161). The concordance rate in primary tumours expressing PD-L1 in <1% or ≥50% of tumour cells was 87.2% (102/117) or 70% (14/20), respectively. In contrast, the concordance rate in tumours expressing PD-L1 in ≥1% to <50% of cells was only 20.8% (5/24). After dichotomising the cases using cutoff values of 1% and 50%, the concordance rate increased to 80.1% (129/161) and 90.7% (146/161) in all paired cases and to 70.4% (19/27) and 85.2% (23/27) in cases with distant metastases, respectively. This study demonstrates that the concordance of PD-L1 expression between primary and metastatic pADC is high when using cutoff values of 1% and 50%. Thus, evaluation of PD-L1 in either primary or metastatic tumours would be helpful for guiding anti–PD-1/PD-L1 immunotherapy in patients with advanced pADC. Highlights: The concordance of programmed death-ligand 1 (PD-L1) expression between primary and metastatic pulmonary adenocarcinoma (pADC) was high when using cutoff values of 1% and 50%. PD-L1 expression of primary and corresponding metastatic pADCs was similar, irrespective of the EGFR mutation status. The concordance of PD-L1 expression was relatively preserved in metachronously or distantly metastatic tumours. PD-L1 expression in primary pADC can be a surrogate for the PD-L1 status in metastatic tumours, and vice versa.